The Tumor Metabolite 5′-Deoxy-5′Methylthioadenosine (MTA) Inhibits Maturation and T Cell-Stimulating Capacity of Dendritic Cells - Brummer, Christina; Singer, Katrin; Henrich, Frederik; Peter, Katrin; Strobl, Carolin; Neueder, Bernadette; Bruss, Christina; Renner, Kathrin; Pukrop, Tobias; Herr, Wolfgang; Aigner, Michael; Kreutz, Marina (Cells, 2024)
Metabolite accumulation in the tumor microenvironment fosters immune evasion and limits the efficiency of immunotherapeutic approaches. Methylthioadenosine phosphorylase (MTAP), which catalyzes the degradation of 5′-deoxy-5′methylthioadenosine (MTA), is downregulated in many cancer entities. Consequently, MTA accumulates in the microenvironment of MTAP-deficient tumors, where it is known to inhibit tumor-infiltrating T cells and NK cells. However, the impact of MTA on other intra-tumoral immune cells has not yet been fully elucidated. To study the effects of MTA on dendritic cells (DCs), human monocytes were maturated into DCs with (MTA-DC) or without MTA (co-DC) and analyzed for activation, differentiation, and T cell-stimulating capacity. MTA altered the cytokine secretion profile of monocytes and impaired their maturation into dendritic cells. MTA-DCs produced less IL-12 and showed a more immature-like phenotype characterized by decreased expression of the co-stimulatory molecules CD80, CD83, and CD86 and increased expression of the monocyte markers CD14 and CD16. Consequently, MTA reduced the capability of DCs to stimulate T cells. Mechanistically, the MTA-induced effects on monocytes and DCs were mediated by a mechanism beyond adenosine receptor signaling. These results provide new insights into how altered polyamine metabolism impairs the maturation of monocyte-derived DCs and impacts the crosstalk between T and dendritic cells.
CRIS-Team Scopus Importer:2025-02-04
Keywords: adenosine; cancer immunosurveillance; dendritic cells; MTA; polyamine; T cell; tumor metabolism